A thorough analysis of the effect of surfactant/s on the solubility and pharmacokinetics of (S)-zaltoprofen - Cuong Viet Pham; Jong-Suep Baek; Jong-Hun Park; Sang-Hun Jung; Jong-Seong Kang; Cheong-Weon Cho (Elsevier, 2019)
Until now, there are no publications about the preformulation studies on (S)-zaltoprofen ((S)-ZPF). Hence, we first investigated the solubility of (S)-ZPF, screened solubilizers and performed the pharmacokinetic study of (S)-ZPF in the presence of the solubilizers. The measurement of the solubility of (S)-ZPF in 26 different solvents was carried out, including d-alpha tocopheryl polyethylene glycol 1000 succinate (TPGS), 2-hydroxypropyl-β-cyclodextrin (HPCD), and mixtures of individual solvent. The plasma concentration of (S)-ZPF and the amount of (S)-ZPF retained in stomach were determined after oral (35.0 mg/kg) and intravenous (5.0 mg/kg) administration. The solubility of (S)-ZPF showed an increase of 484-fold in TPGS compared to its aqueous solubility. There was a significant increase of AUC0-24 h for pure (S)-ZPF in the TPGS group (813.59 ± 64.17 µg⋅h/ml) in comparison with AUC0-24 h in the HPCD group (595.57  ± 71.76 µg⋅h/ml) and water group (465.57 ± 90.89 µg⋅h/ml). In addition, the Tmax of (S)-ZPF in the TPGS group was 2 h, much faster than that in the HPCD or water groups (5.50 or 5.67 h, respectively). This suggested that TPGS played a significant role in the increase of solubility and bioavailability of (S)-ZPF. Keywords: (S)-zaltoprofen, Solubility, Bioavailability, D-alpha tocopheryl polyethylene glycol 1000 succinate, 2-hydroxypropyl-β-cyclodextrin